KAJIAN EMPIRIS TENTANG AUDITOR SWITCHING (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017) - Resita Sekar Palupi; Nora Hilmia Primasari (Universitas Budi Luhur, 2019)
This research is conducted to analyze the influence of audit opinion, financial distress, firm size, size of public accountant firm, and growth of company of auditor switching. The population in this research is used secondary data from the financial statement of companies sector manufacture listed in the Indonesia Stock Exchange in 2015-2017 as many as 149 companies. This research used purposive sampling method and obtained 92 companies sample. The data analysis used logistic regression analysis with program SPSS version 19. The result of this research show that audit opinion and size of public accountant firm have negative effect on auditor switching. While financial distress, firm size, and growth of company have not effect on auditor switching.